Supporting Mothers’ Engagement in a Community-Based Methadone Treatment Program - Nicole Letourneau; Mary Ann Campbell; Jennifer Woodland; Jennifer Colpitts (Nursing Research and Practice)
Unmanaged maternal opioid addiction poses health and social risks to both mothers and children in their care. Methadone maintenance treatment (MMT) is a targeted public health service to which nurses and other allied health professionals may refer these high risk families for support. Mothers participating in MMT to manage their addiction and their service providers were interviewed to identify resources to maximize mothers’ engagement in treatment and enhance mothers’ parenting capacity. Twelve mothers and six service providers were recruited from an outpatient Atlantic Canadian methadone treatment program. Two major barriers to engagement in MMT were identified by both mothers and service providers including (1) the lack of available and consistent childcare while mothers attended outpatient programs and (2) challenges with transportation to the treatment facility. All participants noted the potential benefits of adding supportive resources for the children of mothers involved in MMT and for mothers to learn how to communicate more effectively with their children and rebuild damaged mother-child relationships. The public health benefits of integrating parent-child ancillary supports into MMT for mothers are discussed.